Promotion of methane production by magnetite via increasing acetogenesis revealed by metagenome-assembled genomes. (February 2022) - Yu, Jiafeng; Liu, Jian; Senthil Kumar, P.; Wei, Yunwei; Zhou, Meng; Vo, Dai-Viet N.; Xiao, Leilei
Graphical abstract: Highlights: Diverse mechanisms were proposed to interpret increased methanogenesis by metal oxide. Metagenome-assembled genomes revealed potential functional microbes and pathways. NanoFe3 O4 accelerated acetogenesis instead of acetate oxidation and electron transfer. V3 O7 ·H2 O stimulated both hydrogenotrophic methanogenesis and electromethanogenesis. Abstract: Metal oxides are wildly studied to enhance anaerobic digestion and the methanogenic process, which is generally interpreted by increased direct interspecies electron transfer (DIET). Yet microbial mechanisms involved are under debate. Herein, methane production dynamics were analyzed, and acceleration on biogas accumulation was presented. Complementing previous findings, Fe3 O4 nanoparticles stimulated bacterial fermentation rather than methanogenesis or syntropy between electro-microorganism and methanogen. More importantly, metagenome-assembled genomes proved that Fe3 O4 nanoparticles increased acetogenesis by Parabacteroides chartae, which provided abundant substrates for acetoclastic methanogenesis. Interestingly, the weakly conductive V3 O7 ·H2 O nanowires increased potential hydrogen-producing bacteria, Brevundimonas, and electro-microorganisms, Clostridium and Rhodoferax, which is convenient for conducting DIET. Collectively, conductivity may not be a critical factor in mediating DIET and distinct strategies of metal oxides on methane production propose more possibilities, such as fermentation process.